2021
DOI: 10.1371/journal.pntd.0009425
|View full text |Cite
|
Sign up to set email alerts
|

Profound downregulation of neural transcription factor Npas4 and Nr4a family in fetal mice neurons infected with Zika virus

Abstract: Zika virus (ZIKV) infection of neurons leads to neurological complications and congenital malformations of the brain of neonates. To date, ZIKV mechanism of infection and pathogenesis is not entirely understood and different studies on gene regulation of ZIKV-infected cells have identified a dysregulation of inflammatory and stem cell maintenance pathways. MicroRNAs (miRNAs) are post-transcriptional regulators of cellular genes and they contribute to cell development in normal function and disease. Previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…A number of studies have previously investigated the involvement of miRNAs in ZIKV infection [24,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. These studies have variously identified the regulation of miR-302b, miR-302c, miR-194 and miR-30c in ZIKV-infected human NPCs in vitro [73], miR-146a in ZIKV-infected human microglial cells [75], hsa-miR-101-3p in ZIKV-infected human brain microvascular endothelial cells [67], mir-204 in human fetal neural stem cells as a consequence of ZIKV E protein expression [66], miR-7013-5p in ZIKV-infected fetal mouse neurons [62], miR-9 in ZIKV-infected mice [24] and miR-30e-3p, miR-30e-5p and miR-17-5p in ZIKV-infected astrocytes [70].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have previously investigated the involvement of miRNAs in ZIKV infection [24,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. These studies have variously identified the regulation of miR-302b, miR-302c, miR-194 and miR-30c in ZIKV-infected human NPCs in vitro [73], miR-146a in ZIKV-infected human microglial cells [75], hsa-miR-101-3p in ZIKV-infected human brain microvascular endothelial cells [67], mir-204 in human fetal neural stem cells as a consequence of ZIKV E protein expression [66], miR-7013-5p in ZIKV-infected fetal mouse neurons [62], miR-9 in ZIKV-infected mice [24] and miR-30e-3p, miR-30e-5p and miR-17-5p in ZIKV-infected astrocytes [70].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, previous studies have suggested that overactive immune and cytokine responses are associated with the impairment of astrocytes induced by ZIKV ( Li et al., 2018 ). In addition, pro-inflammatory cytokines, chemokines, and nitric oxide produced by glial cells may be a contributing mechanism of ZIKV causing foetal brain damage ( Bobermin et al., 2020 ), by enhancing neuronal damage and cell death caused by direct ZIKV infection of neurons ( Alpuche-Lazcano et al., 2021 ; Hughes et al., 2016 ; Lin et al., 2017 ; Oh et al., 2017 ). Thus, the DEGs identified in this study should be studied in detail to determine their roles in ZIKV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in animal models have suggested that the main mechanism by which ZIKV causes brain damage in the foetus is through direct neuronal infection. These studies have consistently demonstrated that ZIKV can infect the neurons, resulting in cell death and impaired neurodevelopment, ultimately leading to the development of microcephaly ( Alpuche-Lazcano et al., 2021 ; Hughes et al., 2016 ; Lin et al., 2017 ; Oh et al., 2017 ). In addition to neural cells, studies have shown that glial cells, including microglia and astrocytes, are also significant targets of ZIKV infection in the brain ( Jorgačevski et al., 2019 ; Manet et al., 2022 ; van den Pol et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%